2015
DOI: 10.1007/jhep06(2015)177
|View full text |Cite
|
Sign up to set email alerts
|

Light dark matter candidates in intense laser pulses I: paraphotons and fermionic minicharged particles

Abstract: Polarimetric experiments driven by the strong field of a circularly polarized laser wave can become a powerful tool to limit the parameter space of not yet detected hidden-photons and minicharged particles associated with extra U(1) gauge symmetries. We show how the absorption and dispersion of probe electromagnetic waves in the vacuum polarized by such a background are modified due to the coupling between the visible U(1)-gauge sector and these hypothetical degrees of freedom. The results of this analysis rev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 109 publications
0
15
0
Order By: Relevance
“…The kinetic mixing angle between the hidden and standard photon is naturally small -values χ h ∼ 10 −13 − 10 −2 are typically predicted in the literature [127][128][129][130][131][132][133][134][135][136][137][138]. The mixing leads to a number of observable consequences in laboratory experiments [139][140][141][142][143][144][145][146][147][148][149][150][151][152][153][154][155], astrophysics [156][157][158][159][160][161][162][163][164] and cosmology [165][166][167][168][169][170][171][172][173]…”
Section: Beyond the Qcd Axion Alps And Other Wispsmentioning
confidence: 99%
“…The kinetic mixing angle between the hidden and standard photon is naturally small -values χ h ∼ 10 −13 − 10 −2 are typically predicted in the literature [127][128][129][130][131][132][133][134][135][136][137][138]. The mixing leads to a number of observable consequences in laboratory experiments [139][140][141][142][143][144][145][146][147][148][149][150][151][152][153][154][155], astrophysics [156][157][158][159][160][161][162][163][164] and cosmology [165][166][167][168][169][170][171][172][173]…”
Section: Beyond the Qcd Axion Alps And Other Wispsmentioning
confidence: 99%
“…Conversely, the dispersion equations resulting from the poles associated with the transverse modes Λ ± concide with those found previously in Refs. [67][68][69]:…”
Section: )mentioning
confidence: 99%
“…[67]. Later, in part I of this series [68], a further step was performed by investigating the optical effects resulting from an extended model containing fermionic MCPs and a hidden photon field. There we revealed that, at moderate intensities 10 16 W/cm 2 as provided by the nanosecond frontends of the PHELIX laser [72] and LULI system [73], high-precision polarimetric measurements could improve the existing laboratory upper bounds for the coupling constant of MCPs by an order of magnitude for masses of the order of m ∼ eV.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For studies involving calculations similar to those presented in this paper we refer the reader to [99–102] Given the increasing availability of high-intensity lasers from recent and upcoming experiments [103–109] the study of QED in intense fields to observe both SM and BSM phenomena is of crucial importance. So far, using high-intensity lasers to probe BSM phenomena has mainly be studied theoretically, and then through the coupling to ALPs [110116] and mini-charged particles [117119] to photons. In this paper we study interactions involving electrons and ALPs in intense electromagnetic fields, focusing on the production of ALPs via Compton scattering from electrons in intense laser pulses.…”
Section: Introductionmentioning
confidence: 99%